Determinants of Fiscal Distress in Italian Municipalities - Wildmer Daniel Gregori; Luigi Marattin (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2015)
Fiscal distress of local governments and municipalities is a non-negligible component of the public finance turmoil after the Great Recession. In this paper we consider a dataset of Italian municipalities over the period 2000-2012 and look for the main budget determinants of local default. According to our results the default probability is positively affected by the share of loan repayment over total spending. This result is robust to alternative model specifications as well as inclusion of fixed effects, time dummies and macroeconomic control variables.
Keywords: H72; H74; 330